Epidemiological and clinical analysis of 291 children diagnosed with Chlamydia pneumoniae pneumonia: a 10-year retrospective study in Shijiazhuang, China - Ma, Ran; Zhang, Yingqian; Wang, Yingxue; Liu, Yu; Ba, Chunxiao; Zhang, Mengqiao (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to systematically analyze the epidemiological and clinical features of Chlamydia pneumoniae pneumonia (CPP) in children with community-acquired pneumonia, providing an evidence-based foundation for clinical diagnosis and treatment strategies.MethodsA retrospective analysis was conducted using clinical data from 291 children diagnosed with CPP who had been admitted to Hebei Children's Hospital between January 2015 and May 2025.ResultsThe sex distribution showed a male-to-female ratio of 187:104. The mean age was 8.12 years (range: 1 month–16 years), with an average hospital stay of 7.52 days and a mean total disease duration of 14.81 days. Annual incidence rates exhibited a progressively increasing trend, with peak seasonal occurrence observed during the winter and spring months. Age group analysis revealed the highest prevalence among children aged 7–16 years (198 cases, 68.04%), followed by infants aged 1 month–1 year (65 cases, 22.34%). Cough was the predominant clinical manifestation (141 patients, 98.60%), followed by fever (44.80% of patients; median peak temperature: 38.20 °C). Physical examination revealed pulmonary rales in 288 patients (98.97%). Laboratory findings indicated elevated white blood cell counts with neutrophil predominance, whereas C-reactive protein levels were normal or only mildly elevated. Some patients had abnormalities in coagulation profiles, myocardial enzyme levels, and immune function parameters. Polymicrobial infections were detected in 177 patients (60.82%), with rhinovirus, Haemophilus influenzae, and Streptococcus pneumoniae identified as the primary co-detected pathogens. Age-specific mixed infection patterns were noted. Imaging studies revealed bilateral lung involvement in approximately half of the patients. Bronchoscopic evaluation demonstrated bronchial mucositis with flocculent secretions. Cytological examination of alveolar lavage fluid showed a predominance of neutrophils, monocytes, and phagocytes. Antimicrobial therapy included monotherapy with doxycycline (30.58%), azithromycin (23.71%), and erythromycin (11.34%). During hospitalization, the antibiotic regimen was switched for seven patients due to intolerance or inadequate response to the initial therapy. All patients achieved complete recovery at discharge, and no deaths were recorded.ConclusionsThis study demonstrates that CPP exhibits distinct seasonal and age-related distribution patterns. As the clinical manifestations and routine laboratory markers offer limited diagnostic sensitivity, confirmatory testing is necessary. Our findings support PCR as a valuable diagnostic tool for this purpose.